Comparison of Transthoracic Device Closure and Surgical Repair with Right Submammary or Right Infra-axillary Thoracotomy for Perimembranous VSD - Chen, Qiang; Lin, Ze-Wei; Hong, Zhi-Nuan; Cao, Hua; Zhang, Gui-Can; Chen, Liang-Wan; Yu, Ling-Li; Zhang, Qi-Liang (The Thoracic and Cardiovascular Surgeon, 2019)
Background Transthoracic device closure (TTDC) and surgical repair with right infra-axillary thoracotomy (SRRIAT) or with right submammary thoracotomy (SRSMT) are all the primary alternative treatments for restrictive perimembranous ventricular septal defect (pmVSD). However, few studies have compared them in terms of effectiveness and complications.Methods Patients with restrictive pmVSD undergoing TTDC, or SRRIAT, or SRSMT from March 2016 to February 2017 were retrospectively reviewed in our cardiac center. There were no differences in age (1.3 ± 1.2 vs 1.1 ± 1.1 vs 1.2 ± 1.1 years), gender (35/37 vs 30/33 vs 29/29), body weight (8.3 ± 2.6 vs 8.2 ± 2.4 vs 8.1 ± 2.5 kg), and size of VSD (4.2 ± 1.1 vs 5.2 ± 1.3 vs 5.1 ± 1.2 mm) distribution between the three groups.Results The procedure success rates were similar in the three groups. The TTDC group had the shortest operative time, postoperative mechanical ventilation time, duration of intensive care, postoperative length of hospital stay, medical cost, and length of the incision. There were no significant differences in terms of operative time, aortic cross-clamping time, duration of cardiopulmonary bypass (CPB), blood transfusion volume, mechanical ventilation time, duration of intensive care, duration of hospital stays, pleural fluid drainage, or cost between the SRSMT and SRRIAT groups. No significant differences were noted in terms of major adverse events.Conclusions TTDC, SRRIAT, and SRSMT all showed excellent outcomes and cosmetic appearances for selected VSD patients. TTDC had advantages over SRRIAT and SRSMT in terms of short operation duration and smaller incision size and shorter durations of intensive care and hospital stays.
Keywords: ventricular septal defect; transthoracic device closure; right infra-axillary thoracotomy; submammary thoracotomy